Factors contributing to the vulnerability of healthcare providers in the Bandundu Health Zone and their impact on the ineffectiveness of epidemiological surveillance within the One Health approach - S. L. Manta; A. F. B. Ngwamah; Jean-Paul Koto-Te-Nyiwa Ngbolua; M. Mawunu; B. B. L. Mukandu; B. N. Ntoto (Orapuh Journal, 2025)
Introduction